MnTE-2-PyP Suppresses Prostate Cancer Cell Growth via H2O2 Production - Yuxiang Zhu; Elizabeth A. Kosmacek; Arpita Chatterjee; Rebecca E. Oberley-Deegan (MDPI AG, 2020)
Prostate cancer patients are often treated with radiotherapy. MnTE-2-PyP, a superoxide dismutase (SOD) mimic, is a known radioprotector of normal tissues. Our recent work demonstrated that MnTE-2-PyP also inhibits prostate cancer progression with radiotherapy; however, the mechanisms remain unclear. In this study, we identified that MnTE-2-PyP-induced intracellular H2O2 levels are critical in inhibiting the growth of PC3 and LNCaP cells, but the increased H2O2 levels affected the two cancer cells differently. In PC3 cells, many proteins were thiol oxidized with MnTE-2-PyP treatment, including Ser/Thr protein phosphatase 1 beta catalytic subunit (PP1CB). This resulted in reduced PP1CB activity; however, overall cell cycle progression was not altered, so this is not the main mechanism of PC3 cell growth inhibition. High H2O2 levels by MnTE-2-PyP treatment induced nuclear fragmentation, which could be synergistically enhanced with radiotherapy. In LNCaP cells, thiol oxidation by MnTE-2-PyP treatment was not observed previously and, similarly to PC3 cells, there was no effect of MnTE-2-PyP treatment on cell cycle progression. However, in LNCaP cells, MnTE-2-PyP caused an increase in low RNA population and sub-G1 population of cells, which indicates that MnTE-2-PyP treatment may cause cellular quiescence or direct cancer cell death. The protein oxidative modifications and mitotic catastrophes caused by MnTE-2-PyP may be the major contributors to cell growth inhibition in PC3 cells, while in LNCaP cells, tumor cell quiescence or cell death appears to be major factors in MnTE-2-PyP-induced growth inhibition.